Activity of Aztreonam-avibactam and other β-lactamase inhibitor combinations against Gram-negative bacteria isolated from patients hospitalized with pneumonia in United States medical centers (2020–2022) - Helio S. Sader; Rodrigo E. Mendes; S. J. Ryan Arends; Timothy B. Doyle; Mariana Castanheira (BMC Pulmonary Medicine)
Abstract Background Initial antimicrobial therapy for pneumonia is frequently empirical and resistance to antimicrobial agents represents a great challenge to the treatment of patients hospitalized with pneumonia. We evaluated the frequency and antimicrobial susceptibility of Gram-negative bacteria causing pneumonia in US hospitals. Methods Bacterial isolates were consecutively collected (1/patient) from patients hospitalized with pneumonia and the susceptibility of Gram-negative bacilli (3,911 Enterobacterales and 2,753 non-fermenters) was evaluated by broth microdilution in a monitoring laboratory. Isolates were collected in 69 medical centers in 2020–2022. Aztreonam-avibactam was tested with avibactam at fixed 4 mg/L and a pharmacokinetic/pharmacodynamic susceptible (S) breakpoint of ≤ 8 mg/L was applied for comparison. Carbapenem-resistant Enterobacterales (CRE; isolates with MIC values of > 2 mg/L for imipenem and/or meropenem) isolates were screened for carbapenemases by whole genome sequencing. Results Gram-negative bacilli represented 71.1% of organisms. The most common Gram-negative species were Pseudomonas aeruginosa (22.4% of organisms), Klebsiella pneumoniae (8.8%), Escherichia coli (6.6%), Serratia marcescens (6.2%), Stenotrophomonas maltophilia (4.9%), and Enterobacter cloacae complex (4.8%). Aztreonam-avibactam inhibited 100.0% of Enterobacterales at ≤ 8 mg/L and 99.9% at ≤ 4 mg/L and showed potent activity against CRE (MIC50/90, 0.25/1 mg/L). Ceftazidime-avibactam and meropenem-vaborbactam were active against 89.4% and 88.5% of CREs, respectively. Aztreonam-avibactam retained activity against Enterobacterales non-susceptible to ceftazidime-avibactam and/or meropenem-vaborbactam (n = 19; MIC50/90, 0.25/4 mg/L). The most common carbapenemases were KPC (69.2% of CREs), NDM (9.6%), and SME (4.8%). A carbapenemase gene was not identified in 16.3% of CREs. Ceftazidime-avibactam and meropenem-vaborbactam were highly active against KPC and SME producers but showed limited activity against MBL producers. The most active comparators against CRE were tigecycline (95.2%S), amikacin (73.1%S), and gentamicin (60.6%S). Among Pseudomonas aeruginosa, 79.1% were inhibited at ≤ 8 mg/L of aztreonam-avibactam, 77.2% were meropenem susceptible, and 77.2% were piperacillin-tazobactam susceptible. Aztreonam-avibactam was highly active against S. maltophilia, inhibiting 99.5% of isolates at ≤ 8 mg/L. Conclusions Aztreonam-avibactam displayed potent in vitro activity against a large collection of contemporary Gram-negative organisms isolated from patients hospitalized with pneumonia, including CRE isolates resistant to ceftazidime-avibactam and/or meropenem-vaborbactam. Results of surveillance programs are valuable for planning empiric antimicrobial therapy guidelines and infection control measures.